Особливості оскарження рішень, дій чи бездіяльності прокурора під час досудового розслідування - Олексюк, К.; Oleksyuk, К. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
У статті висвітлено проблеми практичної реалізації положень інституту оскарження рішень, дій чи бездіяльності прокурора під час досудового розслідування. Обґрунтовано окремі пропозиції про внесення змін до Глави 26 Кримінального процесуального кодексу України щодо законодавчого регулювання змісту і форми скарги на рішення, дію чи бездіяльність прокурора під час досудового розслідування. Проаналізовано підстави щодо вдосконалення процедури оскарження рішень, дій чи бездіяльності прокурора під час досудового розслідування. The article deals with the problem of the practical implementation of the provisions of the Institute of appeal against decisions, actions or inaction of the prosecutor during the preliminary investigation. The study of criminal procedure institute appeal against decisions, actions or inaction of the prosecutor during the preliminary investigation singled out problems such as lack of legislative consolidation definitions of the concepts of «other activities» and «proceedings» as well as requirements for the form and content of complaints against decisions, actions or omissions prosecutor during the preliminary investigation. Some proposals on amendments to Chapter 26 of the Criminal Procedural Code of Ukraine on legal regulation of content and form of appeal against a decision, act or omission of the public prosecutor during the preliminary investigation are proved. The reasons for improving the procedure of appeal against decisions, actions or omissions of the prosecutor during the preliminary investigation are analyzed.
Features of Appeal against Decisions, Actions or Omissions of Prosecutor during Pretrial Investigation
Keywords: оскарження рішень, дій та бездіяльності; прокурор; досудове розслідування; кримінальне провадження; права та свободи людини; appealing against decisions, actions or omissions; the prosecutor; pretrial investigation; criminal proceeding; the rights and freedoms of human